Microbial diversity in cutaneous leishmaniasis lesions and potential implications for disease progression and treatment outcomes - Nayana Gunathilaka; Thulangi Siriwardana; Saranga Erathna; Wasana Rodrigo; Hiran Gunasekara; Buthsiri Sumanasena (BMC Research Notes)
Abstract Objective Beyond the parasitic infection in Cutaneous leishmaniasis (CL), secondary bacterial colonization can influence disease chronicity, delay healing, and reduce treatment efficacy. This study investigated the bacterial diversity in CL lesions, its association with lesion duration, and its potential impact on treatment outcomes among Sri Lankan patients. Results Fifteen bacterial species were identified, including both Gram-positive and Gram-negative organisms. Staphylococcus aureus was associated with the longest lesion duration (up to 12 months) and extended treatment (15 cycles of intralesional sodium stibogluconate and cryotherapy). In contrast, species such as Kocuria palustris and Acinetobacter baylyi were linked to shorter treatment durations. Multivariate analysis revealed that lesion type significantly influenced treatment duration (P < 0.05), while larger lesion size and diabetes showed marginal associations with prolonged therapy. The presence of opportunistic and antibiotic-resistant species, particularly S. aureus, suggests a potential contributory role of bacterial co-infections in CL progression and highlights the need to consider their presence in treatment planning. Integrating microbial profiling into clinical protocols may enhance treatment efficacy and inform personalized care strategies. However, the limited sample size and convenience-based recruitment may affect the generalizability of these findings, and the potential influence of bacterial colonization on treatment response warrants further investigation in larger cohorts.